An analysis on Aerodynamics Performance Simulation of NACA 23018 Airfoil Wings on Cant Angles - Setyo Hariyadi (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2017)
Winglet attached on the tip of aircraft wings to increase lift. Mainly, winglet used for increasing aerodynamic efficiency, it decreases induced drag caused by vortex on wings tip. The phenomenon of vortex is collision of high-pressured air below the wings meet the low-pressured air above it that cause turbulence. Induced drag may reach 40% of total drag during cruising, and 80-90% while take off. A procedure to decrease induced drag is using wing tip devices. It used on commercial aircrafts and the most frequently used is blended winglet. Numerical study conducted to examine the best aerodynamic performance of sub-sonic plane wings in angles of attack. Analysis on NACA 23018 airfoil wings with blended winglet on the tip was conducted. Freestream velocity of 40 m/s or Re = 1 × 106, and angle of attack (α) 0o, 5o, 10o, and 15o are used. Evaluation for parameter includes coefficient pressure (Cp), velocity profile, lift, drag, and ratio CL/CD. Obtained contour are pressure contour, velocity, and vorticity. In view of all this, there is increasing performance of aerodynamic with CL/CD ratio of wings with blended winglet and plain wing. Reaching current angle of attack, the function of winglet is gradually decrease.